The mediating role of market orientation on entrepreneurial orientation, absorptive capacity and technological innovation capabilities - Aljanabi, AbdulQadir Rahomee Ahmed; Mohd Noor, Nor Azila (Canadian Center of Science and Education, 2015)
The present study purposes to examine the mediating role of Market Orientation in its nexus among Entrepreneurial Orientation, Absorptive Capacity and Technological Innovation Capabilities among construction SMEs in Kurdistan region of Iraq.Due to the critical role of SMEs in construction industry for the reconstruction of Iraq in general and Kurdistan region in particular, the purpose of present study is to determine whether the Market Orientation has a mediating role in its relation with the examined variables, so as to examine that, the model of present study was developed.To validate the proposed model, self-administered questionnaire were conducted to gathering data from SMEs owners in Kurdistan region of Iraq, 249 questionnaires returned and used for statistical analysis Out of 278 distributed.The outcomes of present research reflect that both of Absorptive Capacity and Entrepreneurial Orientation have significant effect on Technological Innovation Capabilities. Furthermore, the outcomes of present study assert that the Market Orientation has a partial mediation mechanism in the nexus between Absorptive Capacity and Technological Innovation Capabilities.